Towards an understanding of Gambian teachers' lives and careers - Roberts-Holmes, Guy (1999)
This research shows that Gambian teachers have complex reasons for joining and remaining in the teaching profession. It builds upon the literature concerning teachers' professionalism in developing countries by describing and analysing Gambian teachers' professional discourses. This thesis argues that Gambian teachers are active participants who create 'narratives of action' which assert their professionalism. Gambian teachers understand their work as professional through the overlapping moral discourses of nationalism and Islam. These professional discourses sustain and empower Gambian teachers who often work in difficult material conditions.